Pelatihan Penyusunan Kurikulum Pengajian Aisyiyah Kota Medan - Ina Zainah Nasution; Rasta Kurniawati Br. Pinem; Nur Sakinah (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
The existence of a recitation curriculum is not only evidence of good management of the recitation but also an effort to produce higher quality and militant recitation outputs. Based on this, training on the preparation of the Medan City Aisyiyah recitation curriculum was carried out.  The training was carried out using the lecture method by the service team and direct practice in preparing the recitation curriculum. The training was attended by 31 delegates from the Medan City Aisyiyah Branch Manager and 6 members of the Medan City Aisyiyah Regional Leadership Tablighi Assembly. After the training, participants have been able to develop a recitation curriculum. This dedication is important in order to achieve a better recitation management and quality of recitation.